Identificação e prevenção do risco de quedas com aplicação de dupla tarefa em idosos da comunidade - Teixeira, Julianne Pitanga (2021)
Objective: To identify risks for falling and analyze the results of an intervention proposal for the prevention of falls in the elderly with dual-task. Material and Methods: Fifty two volunteers from the Elderly Group in the Laranjeiras -SE, aged range 60 to 85 years, both genders, were submitted to the Dynamic Gait Index (DGI) and the Timed Up and Go (TUG) to determine the risk of falls. In the second step that spent five weeks, the intervention was offered to all volunteers based on the Cawthorne and Cooksey exercises that was choreographed with the music Whiskey a Go-Go and Xote das Meninas. In the third stage the participants were reevaluated with the same protocols used. It adopted the p ≤0.05 for statistical correlations. Results: Around 84.6% were female and 15.4% male; 41 volunteers presented bad performance in the TUG and 20 in the DGI. There was a tendency to correlate between age and TUG (p = 0,06), but there was no correlation between age and DGI (p = 0,26); there was a strong negative correlation between DGI and TUG (p=0,009351). Thirteen seniorswere reevaluated, twelve of them female and one male, aged from 60 to 80. The results of DGI and TUG after the program showed best scores, which means less risk to falls. Conclusion: The proposed intervention with a bimodal task in prevention decreased the falling risks and TUG showed worse performance in older volunteers.